New Horizons for Improving Stroke Prevention and Vascular Outcomes - Cunningham, Muriel (MD Conference Express, 2008)
The prevalence of diabetes has grown at a rapid pace across the world, particularly in the United States. The World Health Organization estimates that the number of people with diabetes will grow globally from 171 million in 2000 to approximately 366 million in 2030 [Wild et al. Diabetes Care 2004], paralleling the global rise in obesity. This article discusses what these trends mean for stroke prevention and vascular health.